An Oxidative Enzyme Boosting Mechanical and Optical Performance of Densified Wood Films (Small 17/2023). Issue 17 (27th April 2023) - Koskela, Salla; Wang, Shennan; Li, Lengwan; Zha, Li; Berglund, Lars A.; Zhou, Qi
Abstract : Densified Wood Films In article number 2205056, Qi Zhou and co‐workers show that cellulose‐oxidizing enzyme lytic polysaccharide monooxygenase (LPMO) can nanofibrillate cellulose microfibril bundles inside the wood cell wall, altering wood microstructure. Therefore, delignified wood can be densified under ambient temperature and low pressure into transparent, foldable, and ultrastrong films. This enzymatic approach offers a sustainable alternative for top‐down modification of wood materials.